Factors Contributing to Burnout and Professional Fulfillment among AAFPRS Members - Morrissette, Margareta; Michalowski, Alexandra; Sclafani, Anthony P. (Facial Plastic Surgery, 2025)
Physician wellness is important for physician engagement and reduction of medical errors 1-6, impacting patient care. A recent survey showed that academic otorhinolaryngologists reported low levels of professional fulfillment and high levels of burnout 7,8. This study explores wellness factors in facial plastic and reconstructive surgery (FPRS).To examine factors associated with fulfillment, burnout, and intent to leave within FPRS.Cross-sectional survey.AAFPRS members completed an anonymous and standardized survey to assess professional fulfillment and burnout. Chi-square testing was used for data analysis.Among 75 respondents (5% response rate), 34% lacked professional fulfillment and 18% experienced burnout, lower than reported rates in academic otorhinolaryngology7. Lack of decision-making power in recruitment/purchasing decisions and uncompensated otolaryngology call were driving factors.Decreased autonomy and extra-subspecialty responsibilities drive burnout, lack of fulfillment, and intent to leave and should be considered in employment arrangements.
Keywords: physician wellness; burnout; professional fulfillment; intent to leave